Long-term outcomes from dose-escalated image-guided intensity-modulated radiotherapy with androgen deprivation: encouraging results for intermediate- and high-risk prostate cancer - Wilcox, Shea W (Dove Medical Press, 2014)
PURPOSE: Dose-escalated (DE) radiotherapy in the setting of localized prostate cancer has been shown to improve biochemical disease-free survival (bDFS) in several studies. In the same group of patients, androgen deprivation therapy (ADT) has been shown to confer a survival benefit when combined with radiotherapy doses of up to 70 Gy; however, there is currently little long-term data on patients who have received high-dose intensity-modulated radiotherapy (IMRT) with ADT. We report the long-term outcomes in a large cohort of patients treated with the combination of DE image-guided IMRT (IG-IMRT) and ADT. METHODS AND MATERIALS: Patients with localized prostate cancer were identified from a centralized database across an integrated cancer center. All patients received DE IG-IMRT, combined with ADT, and had a minimum follow up of 12 months post-radiotherapy. All relapse and toxicity data were collected prospectively. Actuarial bDFS, metastasis-free survival, prostate cancer-specific survival, and multivariate analyses were calculated using the SPSS v20.0 statistical package. RESULTS: Seven hundred and eighty-two eligible patients were identified with a median follow up of 46 months. Overall, 4.3% of patients relapsed, 2.0% developed distant metastases, and 0.6% died from metastatic prostate cancer. At 5-years, bDFS was 88%, metastasis-free survival was 95%, and prostate cancer-specific survival was 98%. Five-year grade 2 genitourinary and gastrointestinal toxicity was 2.1% and 3.4%, respectively. No grade 3 or 4 late toxicities were reported. Pretreatment prostate specific antigen (P=0.001) and Gleason score (P=0.03) were significant in predicting biochemical failure on multivariate analysis. CONCLUSION: There is a high probability of tumor control with DE IG-IMRT combined with androgen deprivation, and this is a technique with a low probability of significant late toxicity. Our long term results corroborate the safety and efficacy of treating with IG-IMRT to high doses and compares favorably with published series for the treatment of prostate cancer.